Application of traditional and reverse labeling approaches to assess dietary bioavailability of metals in biofilms - Yunuo Duan; Shiqi Zhu; Yuxuan Song; Dan Zhu; Mei Zhong; Liqiang Chen; Xia Luo (Environment International, 2025)
The accuracy of stable isotope tracing techniques, traditional and reverse labeling, in evaluating metal bioavailability remains uncertain. This study employed pulse-chase feeding combined with multi-heavy-metal stable isotope labeling to compare the effectiveness of these methods in assessing Zn, Cr, and Pb bioavailability in natural biofilms consumed by the Chinese mystery snail (Cipangopaludina chinensis). Results showed that the waterborne uptake rate constants of 67Zn and 204Pb were higher than the dietborne uptake rate constants (kuf) for both labeling techniques. However, metal accumulation by C. chinensis through dietborne uptake, as determined using reverse labeling, was markedly greater than accumulation via the waterborne uptake route. Reverse labeling kuf values for 67Zn, 53Cr, and 204Pb were 5 %, 12 %, and 21 % higher, respectively, than those from traditional labeling. Despite these differences, both labeling techniques revealed the high bioavailability of heavy metals in biofilms to C. chinensis. Heavy metal assimilation efficiency and ingestion rates were consistent across labeling techniques. Furthermore, neither individual nor multi-metal exposure affected net accumulation, assimilation efficiency, and ingestion rates for metals in biofilms under the same labeling method. This study highlights the utility of stable isotope labeling in bioavailability assessments while emphasizing method variations.